2017
DOI: 10.1097/jcn.0000000000000382
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Baseline Psychological Health on Muscle Pain During Atorvastatin Treatment

Abstract: Background HMG-CoA reductase inhibitors (statins) are generally well-tolerated, with statin-associated muscle symptoms (SAMS) the most common side effect (~10%) of statin users. However, studies and clinical observations indicate that many of the self-reported SAMS appear to be non-specific (i.e., not attributable to statins). Objective Mental health and wellbeing influences self-perception of pain, so we sought to assess the effect of baseline wellbeing and depression on the development of muscle pain with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…Furthermore, we did not find any relationship between level of depression symptoms and report of SAMS. Our results are in line with a randomized trial reporting that higher depression scores within the normal range at baseline did not predict changes in muscle pain severity between atorvastatin and placebo group at 6 months follow-up in patients without cardiovascular disease and depression [ 3 ]. Others have found contrasting results with higher pain scores being associated with higher scores of depression in different patient populations [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, we did not find any relationship between level of depression symptoms and report of SAMS. Our results are in line with a randomized trial reporting that higher depression scores within the normal range at baseline did not predict changes in muscle pain severity between atorvastatin and placebo group at 6 months follow-up in patients without cardiovascular disease and depression [ 3 ]. Others have found contrasting results with higher pain scores being associated with higher scores of depression in different patient populations [ 25 , 26 ].…”
Section: Discussionsupporting
confidence: 91%
“…Second, somatic symptoms, particularly muscle tension, are commonly found in persons with major depressive disorders and anxiety disorders, possibly explained by dysfunctions in serotonergic and noradrenergic systems [ 27 ]. These patients present higher distress scores of anxiety and depression than found in our study and the study by Zaleski et al where patients reported scores within normal range [ 3 ]. This may suggest that in order to identify such associations, distress and associated dysfunction in biological systems may be above a certain threshold.…”
Section: Discussionsupporting
confidence: 49%
See 2 more Smart Citations
“…HS or often called rosella is recognized as a plant, easily grows in tropical and subtropical areas. HS plants have traditionally been involved in food ingredients, flavoring or taste enhancers in the food industry, spices and herbal medicines [14]. In general, the red color of HS petals is due to the compounds delphinidinsambubioside (red pigment) and cyanidin-sambubioside (pink pigment) as an alternative to synthetic dyes.…”
Section: The Content and Benefits Of Hibiscus Sabdariffa As A Herbal ...mentioning
confidence: 99%